Metafilosofía jurídica de los siglos XX y XXI: ¿un concepto analítico de derecho? - López, Nicolás (2016)
This paper aims to offer a metaphilosophical reconstruction of Law in the analytic tradition of the twentieth and twentieth-one century first fifteen years, in order to determine the identity of the “analytic concept of law”. To do that I will usethree argumentative axes. The first will clarify the distinction between the Continental and Anglo-Saxon focuses on twentieth century analytical legal philosophy. The second axis will emphasize the methods and purposes of the latter, from the publication of Hart’s The Concept of Law’s first edition to its second edition in 1994. The third will problematize the existence or non-existence of an analytical concept of Law.